Design of Zero Dispersion Optical Fiber at Wavelength 1.3 m - R. S. Habeb (College of Education for Pure Sciences, 2018)
In this article, an optical fiber was designed with zero- dispersion at wavelength of (1.3 m). The design took into consideration many factors of the fiber, such as; fiber cross- section, fiber material, refractive index. These factor can affect the operation of a fiber in optical communication system. A zero- dispersion fiber was obtained when the core was doped by (1.3%) of GeO2. Implementing the package of computer aided design (OptiFiber 2.0). We were able to attain the optimum values for refractive index core and clad as (1.48 and 1.45) respectively, i.e, a percentage difference of (0.02) for radius (6.728 and 8.46) respectively, for zero- dispersion at wavelength of (1.3 m) that is use in the optical communication.